2018
DOI: 10.1111/coa.13171
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐treatment CD8+ tumour‐infiltrating lymphocyte density predicts distant metastasis after definitive treatment in patients with stage III/IV hypopharyngeal squamous cell carcinoma

Abstract: Higher pre-treatment CD8 tumour-infiltrating lymphocyte density is a useful predictive biomarker for reduced distant metastasis and better prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…Immunohistochemically (IHC) determined high CD8 + T-cell counts are associated with good prognosis in postoperative chemo-radiotherapy treated patients, further indicating its relevance for HNSCC (57). A good prognosis association with IHC CD8 + TIL density was found in patients with oropharyngeal squamous cell carcinoma treated with surgery or (chemo) radiotherapy and in a similarly mixed treatment cohort of hypopharyngeal SCC patients (58)(59)(60).…”
Section: Introductionmentioning
confidence: 90%
“…Immunohistochemically (IHC) determined high CD8 + T-cell counts are associated with good prognosis in postoperative chemo-radiotherapy treated patients, further indicating its relevance for HNSCC (57). A good prognosis association with IHC CD8 + TIL density was found in patients with oropharyngeal squamous cell carcinoma treated with surgery or (chemo) radiotherapy and in a similarly mixed treatment cohort of hypopharyngeal SCC patients (58)(59)(60).…”
Section: Introductionmentioning
confidence: 90%
“…Hypopharyngeal squamous cell carcinoma (HPSCC) is a highly malignant type of head and neck cancer, which is the eighth most common cancer worldwide [1]. Although its incidence is comparatively low, HPSCC is usually diagnosed at an advanced stage due to unapparent early symptoms [2] . Although there are many treatments, such as surgery, concurrent chemoradiation therapy (CCRT) and radiation therapy, the five-year survival rate is less than 35% [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…3,[7][8][9] Although several studies have shown that CD8 + T cells might play an important role in subsets of immune cells, and that HNC patients with higher preexisting CD8+TIL density had more favorable prognosis than those without, there are few reports on the association between locoregional control by RT or CRT and CD8 + TIL density. [10][11][12] Gerber et al reported that the interferon-gamma-mediated immune system is required for effective RT and that elimination of CD8 + cells decreases the antitumor effects of RT. 13 However, some reports have failed to show significant association between CD8+TIL density and locoregional control.…”
Section: Introductionmentioning
confidence: 99%